Sensory Quality of Fresh Noodles Made with Red Dragon Fruit Peel Extract as a Natural Colorant - Sarah Aliyah Fadil; Rahmi Holinesti; Wiwik Gusnita; Riski Gusri Utami (Darul Yasin Al Sys, 2026)
Fresh noodles are widely consumed because of their chewy texture and ease of preparation. Product development in fresh noodles can be enhanced by using natural ingredients as colorants while increasing product value, including red dragon fruit peel, which contains anthocyanin pigments. This study aims to analyze the effect of substituting red dragon fruit peel extract on the sensory quality of fresh noodles, including color, aroma, chewy texture, resistance to breaking, and taste. An experimental design was employed using a Completely Randomized Design consisting of two treatments with three replicates: 150 ml of water as the control treatment (X₁) and 150 ml of red dragon fruit peel extract as the substitution treatment (X₂). Product quality was assessed through an organoleptic test involving 30 untrained panelists using a hedonic scale. Data were analyzed using an independent samples t-test. The findings show that the substitution of red dragon fruit peel extract significantly affected all sensory quality parameters of fresh noodles. Treatment X₂ obtained higher scores than treatment X₁ across all parameters, including color (5.34), aroma (5.00), chewy texture (5.09), resistance to breaking (5.10), and taste (5.11). These results indicate that red dragon fruit peel extract can improve the sensory quality of fresh noodles as a natural colorant. The study concludes that the best sensory quality was achieved through the substitution of 150 ml of red dragon fruit peel extract, suggesting its potential application in fresh noodle product development. Keywords: Fresh Noodles; Red Dragon Fruit Peel Extract; Sensory Quality; Hedonic Test; Natural Colorant